Biomechanical correlates of running performance in active children. Issue 1 (January 2019) - Williams, Sian; Netto, Kevin; Kennedy, Renee; Turner-Bryndzej, Jarrad; Campbell, Ryan; Rosalie, Simon M.
Abstract: Objectives: Examine the running kinematics in healthy, physically active prepubescent children and to determine if specific biomechanical factors correlate with running performance. Design: Cross-sectional study. Methods: Fifteen children (age 9 years, ±11 months) completed a 1 km time trial before undergoing three-dimensional running motion analysis. Results: A strong positive correlation was observed between the biomechanical variables of stride length ( p < .01), contact time ( p < .01) and ankle dorsiflexion angle ( p = .04) with time trial performance. Between variable analyses revealed a strong positive correlation between peak angles of hip adduction and knee flexion. There was no correlation between hip adduction and knee flexion peak angles or the vertical displacement of centre of mass with trial performance. Conclusions: The results of this study show that children with a better time trial performance display longer stride length, shorter contact time and mid or forefoot strike pattern. These findings have implications for targeted technique intervention in children's running training to improve running performance.